PENGARUH KENAIKAN PENGHASILAN TIDAK KENA PAJAK (PTKP) DAN JUMLAH WAJIB PAJAK EFEKTIF TERHADAP PENERIMAAN PAJAK PENGHASILAN (PPH) PASAL 21 PADA KANTOR PELAYANAN PAJAK PRATAMA SERANG - Nurul Susanti; Andi Andi (Tirtayasa Ekonomika, 2018)
This research aims to determine the effect that occurs with the rise of non taxable income rate, and the number of effective taxpayers to the income tax revenue Article 21. This study was conducted in KPP Pratama Serang, the population used is the acceptance of Income Tax (PPh) Article 21 in KPP Pratama Serang and the sample use saturated sample or all population that is income tax (PPh) Article 21 in KPP Pratama Serang every month for period 2014-2016. The analytical method used is Statistical Product and Service Solutions (SPSS) version 2.0. The results of this study reveal that the non-taxable income (PTKP) has a significant effect on the income tax revenue article 21 and has a negative beta value, indicating that the higher rate of non-taxable income, the income tax of Article 21 will decrease. Likewise with the number of effective taxpayers who significantly influence the income tax revenue article 21 and have a positive beta value, indicating that the more effective taxpayers the income tax revenue article 21 will increase. Keywords : Non-taxable income (PTKP), taxpayers effective, income tax receipts (PPh) article 21